Photoacoustic Imaging of Nanoparticle Transport in the Kidneys at High Temporal Resolution. (27th March 2019) - Jiang, Xingya; Du, Bujie; Tang, Shaoheng; Hsieh, Jer‐Tsong; Zheng, Jie
Abstract: Noninvasive monitoring of kidney elimination of engineered nanoparticles at high temporal and spatial resolution will not only significantly advance our fundamental understandings of nephrology on the nanoscale, but also aid in the early detection of kidney disease, which affects more than 10 % of the worldwide population. Taking advantage of strong NIR absorption of the well‐defined Au25 (SG)18 nanocluster, photoacoustic (PA) imaging was used to visualize its transport in situ through the aorta to the renal parenchyma and its subsequent filtration into the renal pelvis at a temporal resolution down to 1 s. High temporal and spatial resolution imaging of Au25 (SG)18 kidney elimination allowed the accurate quantification of the glomerular filtration rate (GFR) of individual kidneys in normal and pathological conditions, broadening the biomedical applications of engineered nanoparticles in preclinical kidney research.